Weathering the storm of COVID-19 pandemic: A cross-sectional survey of reported changes in first contact physiotherapy services in the UK and Australia - Oluwatoyin Adenike Adeniji; Evangelos Pappas; Karen Stenner; Victoria Traynor; Nicola Carey; Theopisti Chrysanthaki (PLoS ONE, 2026)
Limited evidence exists on early COVID-19 related changes in First Contact Physiotherapy Services (FCPS) for musculoskeletal (MSK) patients within the UK primary care (PC) and Australian emergency departments (ED), knowledge that is crucial for understanding their level of responsiveness and readiness for future crises. This study explores the initial changes in FCPS during the COVID-19 pandemic in the UK and Australia. The UK and Australia represent a function of both country and their FCPS context (UK [PC], Australia [ED]). A cross-sectional survey was conducted from January-April 2023. Data were self-reported by physiotherapists in FCPS roles, managing MSK patients in the UK and Australia. Only responses from those who recalled changes in FCPS were included, with 153 participants analysed. Descriptive statistics and two-way ANOVA were used to examine the effects of timing of change, country, and their interaction on readiness and responsiveness to MSK patient needs. Overall, 75.7% of initial changes were perceived to have occurred within three months following the World Health Organisation’s declaration of COVID-19 as a global pandemic. Participants from both countries differed significantly in their perceptions of how COVID-19 affected patient access to FCPS (p < 0.001). Changes in MSK patient presentation to FCPS varied significantly by both the timing of the change and the country (p < 0.001). Similarly, changes in the care delivery platform were significantly associated with the timing of change (p = 0.014) and the country (p < 0.001). While participants’ responses generally indicated inadequate readiness, the overall perceived responsiveness was higher in the UK (using an arbitrary cut-off of ≥50%) compared to Australia. No significant effects of timing or country were found on either readiness or responsiveness. This highlights the need to strengthen FCPS readiness for more responsive future crises. It also suggests the need for contextual considerations when developing readiness strategies.